APLIKASI MONITORING AKSES DAN SHUTDOWN KOMPUTER MENGGUNAKAN SMS - Savitri, Christina Amanda; Sevani, Nina (Teknik dan Ilmu Komputer, 2012)
The development of information technology and the telecommunications quite fast. Their implementation has cleared away to many sectors. One of the implementation that very prominent was Short Message Service (SMS). With his superiority, the SMS showed a system that could control and monitor access from an application, including inside the function to shutdown from one or several computers. The computerâs data that used SMS Gateway will send and show in the website, that played a role as server. With this application system, the user of the computer was given a good solution that was controlling the function of shutdown from a computer or several computers.Â Keywords: monitoring access, shutdown, server,Â  SMS Gateway